2011
DOI: 10.1007/s11427-011-4170-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of aging on EEG after baclofen administration

Abstract: Baclofen is a selective gamma-aminobutyric acid (GABA) type B agonist that may have important medicinal uses, such as in analgesics and drug addiction treatment. In addition, evidence is accumulating that suggests GABAergic-mediated neurotransmission is altered during aging. This study investigated whether baclofen administration (5 mg kg −1 ) induces differential effects on cortical electrical activity with age. Electroencephalograms (EEGs) were recorded from young (3-4 months) and aged (15-17 months) rats, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…A simple diffusion system proposed by Han et al [48] has been validated and can deliver drugs effectively through bypassing the BBB. Fu et al [49] identified a selective GABA B agonist, Baclofen, which can differentially modify cortical electroencephalography activity, elucidating the relationship between GABA B receptor-mediated neurotransmission and aging. Drug addiction is common in pain treatment.…”
mentioning
confidence: 99%
“…A simple diffusion system proposed by Han et al [48] has been validated and can deliver drugs effectively through bypassing the BBB. Fu et al [49] identified a selective GABA B agonist, Baclofen, which can differentially modify cortical electroencephalography activity, elucidating the relationship between GABA B receptor-mediated neurotransmission and aging. Drug addiction is common in pain treatment.…”
mentioning
confidence: 99%